Tuberculosis report among injection drug users and their partners in Kazakhstan. Issue 5 (May 2015) - Hermosilla, S.; El-Bassel, N.; Aifah, A.; Terlikbayeva, A.; Zhumadilov, Z.; Berikkhanova, K.; Darisheva, M.; Gilbert, L.; Schluger, N.; Galea, S.
Abstract Objectives Tuberculosis (TB) is a major threat to global public health. Kazakhstan has the second highest percentage of multidrug-resistant tuberculosis (MDR-TB) cases among incident tuberculosis cases in the world (WHO 2013). A high burden of MDR-TB suggests TB prevention, control, and treatment programs are failing. This study provides an epidemiologic profile of TB among injection drug users (IDUs), a high-risk and chronically underserved population, in Kazakhstan. Study design Cross-sectional study. Methods The authors studied the characteristics and risk environment of IDUs with self-reported previous active TB and their primary sexual partners in Almaty, Kazakhstan. 728 individuals (364 couples) participated in a couple-based study in 2009. Results 16.75% of participants reported at least one positive TB test (x-ray) in their lifetime. In a multivariable logistic regression adjusting for couple-based sampling, persons with positive TB test were significantly more likely to be older (odds ratio (OR) 7.26, 95% confidence interval (CI): 1.73, 30.43), male (OR 5.53, 95% CI: 2.74, 11.16), have a shorter duration of injection drug use (OR 0.17, 95% CI: 0.04, 0.65), have received high social support from their significant other (OR 2.13, 95% CI: 1.03, 4.40) and more likely (non-significantly) to have been incarcerated (OR 7.03, 95% CI: 0.64, 77.30). Conclusions Older men with a history of incarceration and recent injection drug use were more likely to have positive TB test in Kazakhstan. Social network support, while potentially positive for many aspects of population health, may increase risk of TB among IDUs in this context. Public health policies that target high-risk populations and their at-risk networks may be necessary to stem the rise of MDR-TB in Central Asia.